2020
DOI: 10.1021/acssuschemeng.9b06806
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Deconstruction of Sugarcane Bagasse and Straw to Obtain Cellulose Nanomaterials

Abstract: The application of green process engineering strategies to obtain high-value, eco-friendly, and biodegradable materials from residual lignocellulosic biomass can contribute to the sustainability of future biorefineries. Here, we investigated the potential of sugarcane bagasse and straw as lignocellulosic biomass feedstocks to obtain nanocellulose, using the enzymatic hydrolysis route as a platform. The fibers were submitted to a purification process followed by enzymatic hydrolysis with a commercial enzyme coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 133 publications
(75 citation statements)
references
References 61 publications
7
68
0
Order By: Relevance
“…This can be explained by direct competition between these classes of compounds: high production of one generally means low production of the other. In a recent study by Aguiar et al [ 11 ] on the production of CNCs from hydrolysis of pretreated sugarcane and straw, the authors reported the production of a glucose stream with 84 and 75 g/L, respectively; the yield of CNCs production was 11.3% and 12%, respectively, markedly inferior to the levels usually obtained by acid hydrolysis, as pointed out by the authors. Bondancia et al [ 55 ] reported the production of a glucose stream with 91 g/L and the presence of CNF structures in the final spent solid with a CI of 83%, opposed to 72% before hydrolysis.…”
Section: Nanocellulose Production By Enzymatic Hydrolysismentioning
confidence: 85%
See 4 more Smart Citations
“…This can be explained by direct competition between these classes of compounds: high production of one generally means low production of the other. In a recent study by Aguiar et al [ 11 ] on the production of CNCs from hydrolysis of pretreated sugarcane and straw, the authors reported the production of a glucose stream with 84 and 75 g/L, respectively; the yield of CNCs production was 11.3% and 12%, respectively, markedly inferior to the levels usually obtained by acid hydrolysis, as pointed out by the authors. Bondancia et al [ 55 ] reported the production of a glucose stream with 91 g/L and the presence of CNF structures in the final spent solid with a CI of 83%, opposed to 72% before hydrolysis.…”
Section: Nanocellulose Production By Enzymatic Hydrolysismentioning
confidence: 85%
“…Regarding the extraction of CNCs, the most common procedure consists on a sonication step after hydrolysis, allowing an intense fragmentation of NC into particles within a nanoscale size range [ 62 ] and their efficient dispersion, even though some authors have also described its use before hydrolysis [ 67 ]. Some studies have equally reported the application of sulfuric acid [ 42 , 68 ] or other chemicals [ 2 ] after enzymatic hydrolysis or, in total opposite, no treatment after enzymatic hydrolysis [ 11 , 48 , 69 , 70 , 71 ].…”
Section: Nanocellulose Production By Enzymatic Hydrolysismentioning
confidence: 99%
See 3 more Smart Citations